N3 Kanji Learning Patterns Among Japanese Language Education Students at UMY - Yuli Wahyuni; Marahani Evilia Santi (Universitas Negeri Semarang, 2026)
This study examines N3-level Kanji learning patterns among students in the Japanese Language Education Program at Muhammadiyah Universitas of Yogyakarta. Using a descriptive qualitative design, the study involved 16 students who had passed the JLPT N3, selected through a mini-survey and purposive sampling. Data were collected through in-depth interviews and analyzed to identify dominant learning strategies and the internal factors shaping kanji learning at the intermediate level. The findings show that students adopt multimodal learning patterns that combine writing practice, flashcards, digital applications, and audiovisual exposure. These patterns are shaped by both intrinsic and instrumental motivation, as well as by authentic learning experiences. The study also found that students demonstrated higher self-efficacy in kanji Reading tan in writing, with Reading skills developing more readily through contextual exposure, while structured learning patterns tended to produce more stable outcomes tan flexible ones. By focusing on intermediate learners, a group that has received relatively limited attention in previous studies, this study highlights the interaction between multimodal learning strategies and self-efficacy in kanji learning and offers practical implications for designing more effective kanji instruction in Japanese language education at the tertiary level.